Character Formation Model in Islamic Education: A Comparative Study of Hamka’s and Said Nursi’s Concept of Tazkiyatun Nafs - Azmi, Diinu Tsabitul; Azzizah, Syifa Nur; Ikrimah, Diva (Universitas Islam Indonesia, 2025)
Islamic education faces the challenges of modernity and a crisis of values, necessitating an integrated paradigm capable of holistically empowering humanity, particularly in character building. This study aims to comparatively analyze the model of character building through the concept of Tazkiyatun Nafs (self-purification) from Hamka (Indonesia) and Said Nursi (Turkey), using the lens of Islamic Educational Psychology. Employing a comparative literature review method of their key works, the study found that despite both grounding their concepts in tawhid (monotheism), significant methodological differences exist. Hamka emphasizes Tazkiyatun Nafs through the development of good morals (budi pekerti), local wisdom, and rational thinking as a moral fortress. Conversely, Said Nursi focuses his model on spiritual healing (iman-therapy) based on the cosmological reading of the universe (through the Risale-i Nur) to overcome the spiritual diseases of the era of materialism. Comparatively, this model offers a coherent framework for the reconstruction of modern Islamic education. Hamka’s concept is relevant for moral curriculum and social ethics, while Nursi’s concept is crucial for addressing the spiritual crisis and mental health of students. The contribution of this study is the provision of a holistic model for nurturing strong-willed and spiritually healthy individuals (insan kamil) amidst contemporary challenges.